The efficacy of taking traditional Chinese medicine orally in renal interstitial fibrosis: A protocol for a systematic review and meta-analysis. Issue 38 (18th September 2020) - Yu, Guang; Guo, Mao; Zou, Junju; Zhou, Xiaotao; Ma, Yuerong
Abstract: Background: By now, the incidence of chronic kidney disease (CKD) is increasing. The development of various CKD is attributed to the continuous aggravation of renal interstitial fibrosis (RIF) in the process of end-stage renal disease (ESRD). Oral treatment of traditional Chinese medicine (TCM) is one of the therapies for RIF. Randomized controlled trials (RCTs) of TCM treatment RIF have been reported, but its effectiveness and safety have yet been systematically investigated. Therefore, through the systematic analysis and meta-analysis, our study will summarize the effectiveness and safety of oral treatment RIF of TCM, in order to provides scientific reference for clinical practice. Methods: This protocol follows Preferred Reporting Items for Systematic Evaluation and Meta-Analysis. RCTs will be only selected. Such databases as the PubMed, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Excerpt Medical Database (Embase), WanFan Data, Chinese Biomedical Literature Database (CBM), WHO International Clinical Trials Registry Platform will be searched from the inception to June, 2020 to collect the RCTs about taking TCM orally in treating RIF. The literature according to the inclusion and exclusion criteria, data-extracted and the methodological quality evaluated will be performed independently by 2 reviewers. The clinical outcomes including renal function indices (Scr, BUN, 24-hour urinary protein quantity) and Indicators of RIF (TGF-β1, Notch1, Jagged-1). The risk of bias included in the RCTs will be evaluated by the bias risk assessment tool provided in the Cochrane System Evaluation Manual 5.1.0. Review Manager 5.3 provided by the Cochrane collaboration network will be used to process the data. Results and conclusion: Some more targeted and practical results about the efficacy of taking TCM orally in RIF have been provided by our study. The available evidence suggests that the therapeutic effects of combining TCM with Western medicine therapies is much better for RIF than Western medicine therapies only.